The heterogeneity of organizational resilience: exploring functional, operational, and strategic resilience - Hepfer, M; Lawrence, TB (SAGE Publications, 2022)
Research on organizational resilience has grown significantly over the past three decades – but it has done so in an increasingly disorganized fashion. In this article, we present an integrative review of the organizational resilience literature. We synthesize existing research to provide a compelling and generative conceptual foundation for future work in this scholarly area. Our review shows that current research tends to treat organizational resilience as a relatively homogeneous concept. We present an alternative formulation that conceives of organizational resilience as a heterogeneous phenomenon with three main forms – functional resilience, operational resilience and strategic resilience – each with distinctive foundations, dynamics and outcomes. Based on this conceptualization, we develop a cyclical model of organizational resilience that incorporates its heterogeneity and thus allows for more nuanced and precise applications to a variety of contexts and forms of adversity.